Homérico φάρμακα μητιόεντα (Minerva, 2019)
The Homeric expression φάρμακα μητιόεντα is only attested in 8 227. The expression is isolated by its meaning. Μητιόεις;- is an epithet of Zeus. φάρμακα combines with other epithets. The creation of the expression is due to the combination of the formula Διός: μητιόεντος with Διός θυγάτηρ and the secondary separation by the expression έχε φάρμακα. Διός is placed far away from its epithet so that μητιόεις ends up being referred to the closest word φάρμακα.